Abandoning community management for professionalization of water supply in rural Benin - Anna Le Gouais; J. Webster (2011)
How to achieve sustainability in rural water supply is an ongoing challenge and involvement of the community is often seen as crucial for long term success. However, in Benin community management is generally viewed as a disaster after years of poor management, particularly misuse of funds, which has led to unsustainable systems. As a result, the national strategy has shifted away from community management and towards ‘professionalization’ and promotion of the private sector in rural and small town water management. This study analyses the attitudes of key stakeholders, particularly decision makers, towards four forms of management which local authorities can chose to impose, involving community Water User Associations (WUAs) and the private sector to varying degrees. It shows a strong preference towards excluding WUAs by the water services, who advise local authorities, as well as by facilitators. However, some areas continue to include WUAs to avoid conflict with communities.